Assessment of factor productivity and individual input effect on yield and economics of soybean [Glycine max (L.) Merrill]: Assessment of factor productivity and individual input effect on yield and economics of soybean [Glycine max (L.) Merrill] - G SOMANAGOUDA,; HARSHIYA BANU,; R CHANNAKESHAVA,; SHALINI HUILGOL,; G K NAIDU, (Journal of Oilseeds Research, 2023)
In India, the area under soybean is steadily increasing, while production and productivity is comparably low to the world average. To bridge this gap, production factors deciding per-unit production plays a vital role. In the present study, soybean grown with full package (2371 kg/ha) gave significantly higher yield over omission of weed management (1873 kg/ha) and insecticide application (1993 kg/ha). Increase in seed yield with full package over omission of weed management was (21.00%) and omission of insecticide application was (15.94%). The yield gap was higher with weed management (498 kg/ha) and insecticide application (378 kg/ha). Economic gain due to full package was maximum (Net Returns: Rs. 88226/ ha) compared to omission of individual factors.